Structural rearrangements of the spinal-motor segment with prolonged dynamic loads - Сак, Андрей; Антипова, Раиса (Slobozhanskyi Herald of Science and Sport, 2018)
Andrii Sak & Raisa Antypova Purpose: to study structural rearrangements of intervertebral discs and adjacent structures of the spine of rats and the possibility of their preservation under conditions of prolonged dynamic loads in the experiment. Material & Methods: study was performed in an experiment with 90 male rats of the Wistar line, using a training run in a linear treadmill for 20 and 90 days. On the histotopographic sections, after injection into the aortic arch of the animal mascara-gelatin mass, the number of capillary glomeruli in the subchondral parts of the vertebral bodies was counted. Using standard histology methods, structural changes in metaphyseal cartilages, apophyses of vertebral bodies and intervertebral discs of the lumbar spine. Results: the running regimes are defined that cause damage to various structures of the spine and, on the contrary, increase their reliability. Conclusion: it is established that with age the number of blood vessels in the bodies of the vertebrae and capillary glomeruli in their subchondral regions gradually decreases, which is accompanied by a tightening of the intervertebral disk and contiguous structures. Different in intensity and duration of physical activity cause a corresponding change in the number of blood vessels in the vertebrae and, as a consequence, the level of their blood supply.